PENGARUHCORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Patmawati Patmawati (Jurnal Ilmiah Ekonomi Global Masa Kini)
The aim of this research is to empirically prove the effect of corporate social responsibility (CSRD) and good corporate governance (GCG) on firm values with financial performance as intervening variable CSRD is proxied with economic,human rights, environmental, labor practice, society, and product responsibility indicator. Meanwhile, GCG is proxied with institutional and managerial ownership, independent trustee, and audit committee. Population that was studied in this research was manufacturing companies registered in Indonesia Stock Market circa 2009-2013. According to the result obtained from the calculations, the CSRDs (economic, environmental, labor practice, society, product responsibility) positively affect the firm values. The aforementioned indicators also give more insight on improvements on company’s CSR programs although the criteria did not include human right factors according to GRI G4 that hopefully could strenghten investor’s trust on the company. On the other hand, the implementation of GCD also yielded the same effect. The institutional ownership encourages institutional investors to monitor managers’ action, therefore improving control function on the company by the audit commitee. Financial performances as intervening variable was proven as effective tool to mediate CSRD and GCG variables on firm values. The implementations of both were also improved as the financial performance increased, thus positively impacts firm values. We conclude that both CSRD and GCG positively and significantly improve firm values. Financial performances are proven as mediator between both implementations.Key words :Corporate Social Responsibility Disclosure, Good Corporate Governance, Firm Value